Training phoneme blending skills in children with Down syndrome. (October 2013) - Burgoyne, Kelly; Duff, Fiona; Snowling, Maggie; Buckley, Sue; Hulme, Charles
This article reports the evaluation of a 6-week programme of teaching designed to support the development of phoneme blending skills in children with Down syndrome (DS). Teaching assistants (TAs) were trained to deliver the intervention to individual children in daily 10 –15-minute sessions, within a broader context of reading and language instruction. Ten children with Down syndrome (aged 6 years 11 months to 10 years 6 months) took part in the study; assessments of reading and phonological skills were completed at baseline, after an 8-week control period, and after 6-weeks of intervention. Children made significantly greater gains in phoneme blending skills and single word reading during the intervention period than in the control period. Thus, children with Down syndrome can make gains in blending skills, which may generalize to wider literacy skills, following targeted training over relatively short periods.